2021
DOI: 10.1371/journal.pone.0251380
|View full text |Cite
|
Sign up to set email alerts
|

Trends in malaria prevalence and risk factors associated with the disease in Nkongho-mbeng; a typical rural setting in the equatorial rainforest of the South West Region of Cameroon

Abstract: Globally, malaria in recent years has witnessed a decline in the number of cases and death, though the most recent world malaria report shows a slight decrease in the number of cases in 2018 compared to 2017 and, increase in 2017 compared to 2016. Africa remains the region with the greatest burden of the disease. Cameroon is among the countries with a very high burden of malaria, with the coastal and forest regions carrying the highest burden of the disease. Nkongho-mbeng is a typical rural setting in the equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
(47 reference statements)
13
12
1
Order By: Relevance
“…2,29 Our finding is similar to the report of Umma et al 30 who reported malaria prevalence of 72.2% among febrile children attending Aminu Kano Teaching Hospital in Kano, Northwestern Nigeria. However, the malaria prevalence in this study is higher than previous reports from other parts of Nigeria like Ibadan, 31 Borno, 32 Lagos, 33 Anambra, 34,35 Enugun, 36 Ogun, 37 Jos, 38,39 Sokoto 40 and other malaria-endemic countries such as Cameroon, 41,42 Ethiopia, 43,44 Ghana, 45 Malawi 46 and Rwanda. 47 On the other hand, a higher malaria prevalence of 80.5% and 78% were reported among children in Ogun, southwestern Nigeria and Al Sabah, South Sudan, 48,49 respectively.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…2,29 Our finding is similar to the report of Umma et al 30 who reported malaria prevalence of 72.2% among febrile children attending Aminu Kano Teaching Hospital in Kano, Northwestern Nigeria. However, the malaria prevalence in this study is higher than previous reports from other parts of Nigeria like Ibadan, 31 Borno, 32 Lagos, 33 Anambra, 34,35 Enugun, 36 Ogun, 37 Jos, 38,39 Sokoto 40 and other malaria-endemic countries such as Cameroon, 41,42 Ethiopia, 43,44 Ghana, 45 Malawi 46 and Rwanda. 47 On the other hand, a higher malaria prevalence of 80.5% and 78% were reported among children in Ogun, southwestern Nigeria and Al Sabah, South Sudan, 48,49 respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…This is higher than the 750 parasite/μL of blood reported in Ogun state, Nigeria 48 but lower than the geometric mean parasite density reported in studies conducted in Ghana, 51 Sudan, 52 and Cameroon. 42 The high geometric mean parasite density of malaria disease among children in this study could be as a result of constant exposure to mosquito bite without any major prevention and care intervention program which is a common characteristic of resource-poor settings. Furthermore, our findings revealed that P. falciparum was the only Plasmodium species encountered in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Our findings were similar to those of other studies in Cameroon; 10.8% of asymptomatic malaria among school children in the Nkonghombeng rural area of the Southwest Region [53], 14.1% among HIV patients in Limbe [54], 17.6% amongst children from five epidemiological strata of malaria in Cameroon [10], and 18.9% in Douala [18]. Out of Cameroon, it was similar to the 16.4% among U5C in the meso-endemic Iguhu of Western Kenya [48], 18.4% among asymptomatic migrant labourers in Armachiho District -Ethiopia [9], and the 1 -19% among people in the Amazonian indigenous Yanomami community area [55].…”
Section: Prevalence Of Malaria/anaemia In Association With General Ch...supporting
confidence: 92%
“…This could be attributed to existing social behavioural differences, such as more males engaging in nocturnal outdoor activities, which kept them out of the intervention coverage and low LLIN use when compared to female patients. Low LLIN use and participation in activities outside of intervention coverage [ 32 34 ] have been demonstrated to increase exposure to biting by infected female Anophelines [ 25 , 35 , 36 ]. As a result, this study findings corroborate previous research that reported a high prevalence of P. falciparum slide positivity in males [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%